PENGARUH PENGETAHUAN PRODUK DAN PROMOSI TERHADAP MINAT MENGGUNAKAN LAYANAN PEGADAIAN SYARIAH DI KOTA JAMBI - Nurni Lamsari; Rafidah Rafidah; M. Taufik Ridho (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
The high level of living needs that must be met is a burden that every earning individual must go through and not all of their needs are met. With the existence of sharia pawnshops can help economic problems in each individual. Therefore, this research aims to determine the influence of product knowledge and promotions on interest in using sharia pawnshop services among people in the city of Jambi. This study uses a quantitative research method with a descriptive approach. Sampling of 100 people using the Slovin formula approach. Data collection by observation and questionnaires. Data were analyzed using instrument test analysis, classical assumption test, hypothesis test, simultaneous test and coefficient of determination test. Based on the results of this study, there is a positive and significant influence between product knowledge and promotion on interest in using sharia pawnshop services. Using the t test the significance value of product knowledge is 0.001 <0.05 and the tcount > ttable 3.513 > 0.1984723, the promotion significance value is 0.000 <0.05 and the tcount > ttable 5.010 > 0.1984723. Simultaneously or together, a positive and significant effect can be seen from the f test, namely fcount > ftable or 53.690 > 3.090187 and a significant value of 0.000 <0.05. Based on the R Squre test results, the R2 value is 0.525 or 52.5%, the remaining 48.5% is influenced by variables outside this study. With this, sharia pawnshops are expected to further increase promotions so that the public can find out what products are offered by sharia pawnshops.